2023
DOI: 10.3390/biomimetics8070555
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Experimental Validation of a Biomimetic Stubble-Cutting Device Inspired by a Leaf-Cutting Ant’s Mandibles

Hongyan Qi,
Zichao Ma,
Zihe Xu
et al.

Abstract: Under the conditions of conservation tillage, the existence of the root–soil complex greatly increases the resistance and energy consumption of stubble-cutting blades, especially in Northeast China. In this research, the corn root–soil complex in Northeast China was selected as the research object. Based on the multi-toothed structure of the leaf-cutting ant’s mandibles and the unique bite mode of its mandibles on leaves, a gear-tooth, double-disk, bionic stubble-cutting device (BSCD) was developed by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…can greatly enhance their performance due to considerable reduction in turning/milling/drilling force and temperature, resulting in major reduction in tool wear [138,270,279]. Some existing examples and nature inspirations reported are derived from python skin [123,274], sea urchin teeth [44,272,273], crab or dung beetle claw and legs [21,41,228,280], mole pelt claw [24,36,268,281,282], pangolin claw [24,52,226,277], wood wasp ovipositors [265,280], earthworm skin [262], seashell [283,284], human teeth [285,286], sunflower seeds [259], corn/maize leaf [287][288][289], badger teeth [36,44,271,273,285], etc. Figure 18 shows the self-sharpened serrated edges in different biological species.…”
Section: Bioinspired Design Of Tools For Cutting or Machiningmentioning
confidence: 99%
“…can greatly enhance their performance due to considerable reduction in turning/milling/drilling force and temperature, resulting in major reduction in tool wear [138,270,279]. Some existing examples and nature inspirations reported are derived from python skin [123,274], sea urchin teeth [44,272,273], crab or dung beetle claw and legs [21,41,228,280], mole pelt claw [24,36,268,281,282], pangolin claw [24,52,226,277], wood wasp ovipositors [265,280], earthworm skin [262], seashell [283,284], human teeth [285,286], sunflower seeds [259], corn/maize leaf [287][288][289], badger teeth [36,44,271,273,285], etc. Figure 18 shows the self-sharpened serrated edges in different biological species.…”
Section: Bioinspired Design Of Tools For Cutting or Machiningmentioning
confidence: 99%
“…This is attributed to the anchoring effect of roots within the soil, which imparts greater stability and mechanical strength to the root−soil complex. Qi et al [ 89 ] were inspired by the multi-toothed structure and biting mode of the mandibles of leaf-cutting ants and designed the cutter and motion structure of the stubble-cutting device for cutting the root−soil complex, as shown in Figure 9 b. Field experiments showed that, at 240 rpm rotary speed, compared to the traditional power straight blade, the torque of cutting was reduced by 15.4%, while the power decreased by 11%.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
“…The curvature of these tooth-like structures varies over a broader range, resulting in soil-engaging components bearing greater pressure per unit area. This maximizes soil stress concentration, enhances the soil crushing effect, and improves the cutting and fracturing of soil [ 89 ].…”
Section: Analysis Of Optimizing Performance Mechanisms Of Biomimetic ...mentioning
confidence: 99%
See 1 more Smart Citation